1989
DOI: 10.1079/bjn19890123
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of 67Cu in blood, bile, urine and faeces from 67Cu-primed lambs: effect of 99Mo-labelled tetrathiomolybdate on the metabolism of recently stored tissue 67Cu

Abstract: 1. The relative importance of excretory routes in the removal of recently stored 67Cu following tetrathiomolybdate (TTM) administration was studied. Lambs fed on either 5 mg Cu/kg dry matter (DM) or 35 mg Cu/kg DM, were primed intravenously (iv) with 87Cu and challenged 27 h later with gsMo-labelled TTM given either iv or intraduodenally (id). The profiles of "Cu and esMo and of Cu and Mo in blood, bile, urine and faeces were measured.2. Level of dietary Cu and route of administration of "Mo-TTM affected the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…This is the first study that has examined the effect of dietary Mo and S on biliary Cu excretion in ruminants. Preliminary findings were previously reported (Gooneratne et al 1987;1988b).…”
supporting
confidence: 77%
“…This is the first study that has examined the effect of dietary Mo and S on biliary Cu excretion in ruminants. Preliminary findings were previously reported (Gooneratne et al 1987;1988b).…”
supporting
confidence: 77%
“…Experimental animals Four female lambs drawn from a pool of eight cross-bred female lambs (17-22 kg) were used in the present study. The procedures for housing, feeding, bile duct and duodenal cannulation techniques, period of time allowed for recovery from surgery, bile flow stabilization period and sampling schedule to determine baseline values of Cu in plasma, bile, urine and faeces before radiotracer studies, have been reported (Gooneratne et al 1989). The lambs received either 5.1 mg Cu/kg (lamb nos.…”
Section: Methodsmentioning
confidence: 99%
“…carried out to evaluate the fate of Cu in the long-term Cu storage compartment, and to determine the effectiveness of TTM in the removal of Cu from this compartment. Systemic effects of TTM and relative efficiencies of body Cu removal via the different excretory pathways were examined, with special emphasis on deviations in mechanisms of biliary Cu excretion compared with the mechanisms proposed for bile Cu excretion from the shortterm Cu storage compartment (Gooneratne et al 1989).…”
mentioning
confidence: 99%
“…Cytochrome oxidase activity of the intestinal epithelial cells was reduced indicating local interference in the^availability of Cu to these cells. Since S'-may be generated from TM, it seems possible that S'-may have inhibited cytochrome oxidase directly (Nicholls 1975 (trans-biliary, transhepatocellular and hepatolysosomal) were the same either after o'Cu or after TM4 administration (Gooneratne et al 1989c). However, during removal of Cu from a long-term storage compartment, the transhepatocellular pathway appeared absent, while transbiliary and hepatolysosomal pathways were still operative (Gooneratne et al 1989d).…”
Section: Canadian Journal Of Antmal Sciencementioning
confidence: 99%